Dietary supplementation with Rehmannia glutinosa affects the composition of intestinal microorganisms in common carp. (5th September 2018) - Chang, Xulu; Feng, Junchang; Guo, Xiangrui; Huang, Mengyuan; Nie, Guoxing; Zhang, Jianxin
Abstract : A feeding experiment was conducted to investigate the effects of Rehmannia glutinosa (RG) on the bacterial, archaeal, and fungal community composition in the gut of common carp ( Cyprinus carpio L.). Common carp were given a control diet and an RG‐supplemented diet (basal diet plus 4% prepared Rehmannia root powder) over a period of 80 days. Our results indicated that the bacteria Fusobacteria, Proteobacteria, and Bacteroidetes ; the archaea Crenarchaeota and Euryarchaeota ; and the fungi Basidiomycota are the most abundant microbial taxa in the gut of common carp. Compared with the common carp fed a control diet, the common carp fed an RG‐supplemented diet contained a higher content of Akkermansia sp., and a lower proportion of Aeromonas sp. These results indicate that the consumption of a diet containing RG can lead to the accumulation of more beneficial microorganisms while inhibiting the growth of potential pathogens. Moreover, Crenarchaeota, the methanogenic, and Basidiomycota were detected in this study, these populations may be of high physiological relevance in carp because they have been implicated in human health and disease. Our results suggest that an RG‐supplemented diet changes the intestinal microbial composition of common carp, which could have positive effects on the immune response of carp.